Investigation of thin gate-stack Z2-FET devices as capacitor-less memory cells. (September 2019) - Navarro, S.; Marquez, C.; Lee, K.H.; Navarro, C.; Parihar, M.; Park, H.; Galy, P.; Bawedin, M.; Kim, Y.T.; Cristoloveanu, S.; Gamiz, F.
Abstract: Thin-oxide Z 2 -FET cells operating as capacitor-less DRAM devices are experimentally demonstrated. Both the retention time and memory window demonstrate the feasibility of implementing this cell in advanced 28 nm node FDSOI technology. Nevertheless a performance drop and higher variability with respect to thicker oxide Z 2 -FET cells are observed.